2020
DOI: 10.1177/2158244020962776
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity Lens Embedded in the Public Health Policies of Saudi Arabia: A Qualitative Document Analysis

Abstract: In the Kingdom of Saudi Arabia (KSA), no studies have been documented to analyze the equity aspects of public health policies. The aims of the study were to identify policy documents in the KSA relevant to public health and to explore whether these include an equity approach. Twenty health-related documents were identified from various ministries’ websites and analyzed through directed content analysis. The results showed that the term “equity” was neither defined nor explained in the documents and suggestions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…While the term "equity" is part of the health Law of Governance in the Kingdom, there is no standard term for equity in Arabic. Health equity is a concept that has not been used traditionally or de ned in health policy documents in Saudi Arabia (20).…”
Section: Introductionmentioning
confidence: 99%
“…While the term "equity" is part of the health Law of Governance in the Kingdom, there is no standard term for equity in Arabic. Health equity is a concept that has not been used traditionally or de ned in health policy documents in Saudi Arabia (20).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of policy document analysis have been applied to the health research field. For instance, some scholars used qualitative document analysis to discuss the equity embedded in public health policies [ 61 , 62 ]. Other scholars have applied bibliometric analysis, a quantitative method widely used in literature review research, to characterize the evolution of health-related policies [ 63 , 64 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Jalam et al (2020) analyzed relevant policy document on Nigeria's desertification control via QDA, and found that the integration of sustainable practice across the policy cycle is responsible for the participation of civil society organizations. Also, QDA on twenty health-related policy documents in Saudi Arabia indicated that inequity of healthcare in Saudi Arabia was quite serious, but lacked suggestions to improve health equity ( Eklund Karlsson et al, 2020 ). To evaluate the implementation of national health policy for primary health care, Dominguez-Cancino et al (2020) analyzed thirteen primary health care policy documents in Chile via QDA.…”
Section: Related Workmentioning
confidence: 99%